mexicano en el siglo XXI Fragmentation, Failed Condition and Dispossession: the case of the Mexican State in the 21st century - Odín Ávila (Revista Kavilando, 2018)
The concept of accumulation by dispossession orchestrated by criminal organizations is an ideal reflection to explain theft, fraud, depredation, pillage, punishment and enclosure of territories to force populations to cultivate drugs or to take possession of and / or control sectors productive (agriculture and services) to collect floor rights (taxes) and thus, reproduce illicit businesses that potentiate its value chain, from primary production, to its commercialization. The conjecture that sustains this work, is to explain, how the drug business is part of the accumulation by dispossession, both in form and content, these shady and illegal businesses function as a capitalist, economically rational enterprise that exploits the power of work and market natural goods.